Pedoman Menilai Ajaran Sesat Menurut Rasul Yohanes - Busno, Busno; Barnabas, Barnabas; Hendrikus, Hendrikus (Sekolah Tinggi Teologi Berita Hidup, 2025)
The heresy that has arisen among Christians or Christianity dates to the time of the Apostles, throughout the history of the church and continues to this day, even to the end of time. The true church, as the body of Christ on earth, must fight against it tenaciously, as the Apostles did. This study examines how to judge whether a teaching is called heretical or not, especially by observing the instructions given by Apostle John in his letters. The goal is to provide guidelines for Christians to be able to respond critically to various teaching winds that arise and are not easily misled. This study uses a literature study method with a hermeneutic approach in analyzing the books of I and II John. In addition, other subpoenas and literature from online journals are also used to enrich research data. The findings of the study provide some clues from the Apostle John to judge a heresy, namely that heresy denies the existence of a biblical God who reveals Himself in three persons, rejects the humanity of Christ, opposes the authority and teachings of the Apostles, and attaches importance to worldly things.